2018
DOI: 10.1055/s-0038-1673656
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Population-Based Study of Trends in Operative Vaginal Delivery Compared to Cesarean Delivery Rates in Low- and Middle-Income Countries, 2010–2016

Abstract: Objective Few data are available on cesarean delivery and operative vaginal delivery trends in low- and middle-income countries. Our objective was to analyze a prospective population-based registry including eight sites in seven low- and middle-income countries to observe trends in operative vaginal delivery versus cesarean delivery rates over time, across sites. Study Design A prospective population-based study, including home and facility births among women enrolled from 2010 to 2016, was performed in comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 13 publications
(22 reference statements)
0
21
0
1
Order By: Relevance
“…Several studies have reported low incidence of AVD in many countries, including low-income countries of sub-Saharan Africa [1,3,9,10,12]. However, the recent increase in Caesarean section rates in many countries has not resulted in any significant improvement in neonatal outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported low incidence of AVD in many countries, including low-income countries of sub-Saharan Africa [1,3,9,10,12]. However, the recent increase in Caesarean section rates in many countries has not resulted in any significant improvement in neonatal outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…While caesarean section rates have increased dramatically worldwide in the last decades [3][4][5][6], AVD is significantly under-utilized, particularly in sub-Saharan Africa; accounting for a meager 1% of institutional births [7][8][9][10]. Indeed, the decreasing trend in the utilization of AVD in low and middle-income countries has largely been attributed to decreasing experience with skills required for AVD [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Caesarean section rate has been varying in different parts of the world. In many countries, the rate of caesarean sections has reached 25% [6]. Likewise, most recent data indicate that the current rate of caesarean sections is 19.6% in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, Pakistan is amongst those developing countries that are responsible for the worldwide increase in caesarean sections [7]. Despite certain side effects and post-delivery complications, caesarean sections are emerging as the rst choice for childbearing worldwide [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its advantages, IVD is hardly used in many LMIC (<1% of institutional births), which is very different from many high‐income European countries that often have frequencies above 15% . A cross‐sectional health facility assessment in 40 countries in Latin America, sub‐Sahara Africa and Asia revealed that reasons for not using IVD were equipment related; lack of staff training; issues with authorisation of human resources and the perception amongst staff that no women with an indication for IVD had presented to the health facility .…”
Section: Introductionmentioning
confidence: 99%